Cancer theory faces doubts - Ledford, Heidi (Nature (London), 2011)
OSI Pharmaceuticals, based in Melville, New York, is already pursuing EMT inhibitors as possible cancer treatments, as are several academic labs. "EMT is really becoming a popular subject," says Shoukat Dedhar, a cancer researcher at the British Columbia Cancer Research Centre in Vancouver and a self-avowed convert to the hypothesis. CONFLICTING IDEAS Champions of the EMT-metastasis hypothesis, including leading cancer biologist Robert Weinberg at the Whitehead Institute for Biomedical Research in Cambridge, Massachusetts, say that this may simply be because EMT is so transient - once a metastatic cell has invaded a new tissue, its mesenchymal features melt away.